P-G5 Differential immune response to HCV peptides as cancer-progression biomarkers of HCV-infections. (April 2018) - Tornesello, AnnaLucia; Reimer, Ulf; Holenya, Pavlo; Knaute, Tobias; Tornesello, MariaLina; Maria Buonaguro, Franco
Abstract : HCV infections are the main cause of chronic liver disease and in part of lymphoproliferative disorders. Most HCV infections (>90%) determine chronic hepatitis, 30% of which progress to liver cirrhosis and 3% annually to Hepatocellular Carcinoma (HCC). The progression rate is mainly articulated in low (>40 years) and high (<10 years) speed progressors, with the latter being associated to male gender, <40 years of age, >150mL daily alcohol consumption. Current progression markers are mainly based on biochemical evaluation of liver damage (elevation of alanine and aspartate transaminases) and inflammation (elevation of alpha-fetoprotein). Such markers are not specific and elevated also for other infections (ie, HBV and HCMV) or metabolic disorders (ie, steatosis). Specific HCV-related markers would be relevant to identify HCV co-factors and to select high priority people for direct anti-viral treatment. To identify HCC progression markers, samples from HCV+ patients at different infection stage have been analyzed on the HCV-peptide platform newly developed by JPT Peptide Technologies GmbH (Germany). It covers the complete HCV-protein arrays with >3000 overlapping 15-amino-acid-long peptides from all structural and non structural HCV proteins. The currently available data (from 7 HCV+ asymptomatic, 5 HCV+ with cryoglobulinemia, 9 HCV cirrhosis/HCC and 5 HCV− patients) demonstrates that in asymptomatic patients the level of anti-HCV is in general very low (including anti-capsid/core proteins), while high levels of immunoresponse anti-non-structural proteins is present in patients with liver cancer. Confirmation of such data would support the anti-non structural response as biomarker of cancer progression in HCV+ patients.